Conceptualizing Masculinity in Female-to-Male Trans-Identified Individuals: A Qualitative Inquiry - Vegter, Vanessa (Canadian Journal of Counselling and Psychotherapy, 2012)
<span lang="EN-GB" style="color: black; font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: "ヒラギノ角ゴ Pro W3"; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"><span style="line-height: 115%; font-family: "Times New Roman","serif"; font-size: 12pt; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-size: 11.0pt; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi;">A non-normative gender identity raises questions concerning widely accepted theories of gender that prevail in Western society. These theories are founded upon dichotomous models of gender identity that are posited as having a direct relationship to binary biological sex. The purpose of this qualitative study was to explore how individuals who have transitioned from female to male (FTM) conceptualize their masculinity outside of the constraints of the binary model. Six FTM participants who had transitioned to some degree were interviewed. Through the exploration of the participants’ lived experience and understanding of their male identities, 5 major categories, 12 major themes, and 48 subthemes emerged. A process entitled Embodying a Male Identity was revealed. According to this process, the FTMs in this study embodied a male identity through a variety of experiences that serve to align external physiology with internal self. This process suggests that masculinity, which is often interpreted in the social realm as a validation of maleness, is not a requirement for, or a product of, a male gender identity. Rather, masculinity (alongside femininity) is viewed by participants as a set of traits that vary naturally in all humans (regardless of gender).